Pembagian Harta Peninggalan Dengan Pertimbangan Kemampuan Ahli Waris - Umar Faruq (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2020)
The process of passing on or transferring family assets to children, to family descendants begins when the parents are still alive. The transfer of rights to assets in Muslim communities in Indonesia, apart from being in the form of inheritance, is also known in the form of gifts and wills. Looking at the phenomenon in Langkap village, researchers are interested in the practice of dividing inheritances, gifts and wills with economic considerations for the heirs, civil servant heirs will receive a smaller amount of inheritance than non-civil servant heirs. The distribution is based on the agreement of the heirs because this distribution prioritizes the principle of deliberation and consensus between the heirs. It should be noted that the phenomenon of inheritance distribution that occurs in Langkap village adheres to one of the hereditary systems that exist in Indonesia, namely the bilateral system. This bilateral system attracts both the father's and mother's lineages, so that in this kind of family, in essence, there is no distinction between the heirs from the mother's side or the father's side. The reasons for dividing inherited assets based on economic considerations include, among other things, a sense of compassion, avoiding inequality. economy, and avoid conflict. Ways to avoid conflict can be done by dividing inheritance assets taking into account the economic considerations of the heirs, dividing inheritance assets equally, deliberation and handing over problems to the village.